Skeletal muscle MRI magnetisation transfer ratio reflects clinical severity in peripheral neuropathies. Issue 1 (25th May 2011) - Sinclair, C D J; Morrow, J M; Miranda, M A; Davagnanam, I; Cowley, P C; Mehta, H; Hanna, M G; Koltzenburg, M; Yousry, T A; Reilly, M M; Thornton, J S
Abstract : MRI may provide treatment outcome measures in neuromuscular conditions. The authors assessed MRI magnetisation transfer ratios (MTRs) in lower-limb musculature as markers of pathology in peripheral neuropathies and compared the findings with associated clinical data. Ten patients with Charcot–Marie–Tooth disease type 1A (CMT1A) and nine patients with chronic inflammatory demyelinating polyneuropathy (CIDP) were compared with 10 healthy subjects. The MTR in the calf muscles was significantly lower than controls in the two patient groups (both p<0.001). The median MTRs (IQR) were 50.5(1.6) percentage units (p.u.) (control), 41.5(10.6) p.u. (CMT1A) and 39.3(8.7) p.u. (CIDP). Moreover, anterior lower leg MTR correlated strongly with strength of ankle dorsiflexion, measured with the Medical Research Council scale, in CIDP (ρ=0.88, p<0.001) and also in CMT1A (ρ=0.50, p<0.05), where MTR also showed an association with disease duration (ρ=−0.86, p<0.001). Short tau inversion recovery MRI of the same muscles showed abnormalities associated with regions of reduced MTR (p<0.001), and MTR was also reduced in other muscles otherwise deemed normal appearing (p<0.001), indicating that MTR may be more sensitive to muscle damaged by denervation than conventional MRI. The significant reductions in muscle MTR in peripheral neuropathies and the associated correlations with clinical measures indicate that MTR has potential as an imaging outcome measure in future therapeutic trials.